Prediction of Asiatic Acid Derivatives Affinity Against SARS-CoV-2 Main Protease Using Molecular Docking - Musfiroh, Ida; Resti Azura, Alia; Rahayu, Driyanti (Pharmaceutical Sciences and Research, 2020)
COVID-19 is a pandemic that currently occurs in almost all parts of the world, caused by a new coronavirus species that can infect humans, namely SARS-CoV-2. To date, there is no effective drug to treat COVID-19. There are studies proving that the secondary metabolites of pentacyclic triterpenes have antiviral activity, one of which is asiatic acid. The aims of this study are to obtain the affinity and interactions of asiatic acid derivative structures in inhibiting the main protease of SARS-CoV-2. The research method was molecular docking of asiatic acid and its derivatives against the main protease of SARS-CoV-2 (6LU7) consisting of ligand and receptor preparation, identification of active site, and molecular docking simulation. The results of this study indicate that asiatic acid derivative AA9 has the best affinity in inhibiting the main protease of SARS- CoV-2 with binding free energy value (∆G) of -9.90 kcal/mol, compared with favipiravir which has ∆G value of -4.58 kcal/mol. AA9 also has an interaction with the main protease of SARS- CoV-2 through hydrogen bonds with Gly143. This present study showed that asiatic acid and its derivatives have a higher binding affinities to SARS-CoV-2 main protease compared to favipiravir.